Aksesibilitas Perempuan Terhadap Lembaga Keuangan Mikro - Roswita Hafni; Prawidya Hariani RS; Almira Thalita (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
The role of microfinance institutions in boosting the people's economy is urgently needed. Providing access to microfinance is considered one of the key programs for efforts to eradicate poverty, especially since so far the poor have faced many obstacles in accessing other banking systems or institutions. One of the microfinance products rolled out is PT. Permodalan Nasional Madani Mekaar (PT. PNM Mekaar) which was established in 2015 with more than 10.8 million customers. This research was conducted with the aim to find out how customers' perceptions of PT. PNM Mekaar and its contribution to micro business income before and after getting financing. The sample is entrepreneurs who are classified as micro businesses who are PNM Mekaar customers in Medan, Johor, totaling 43 customers. The data used are primary data, sourced from the results of distributing questionnaires and secondary sources from the Central Statistics Agency (BPS), the Financial Services Authority (OJK). This method uses descriptive analysis method and inductively with paired difference test. The results showed that there was a significant influence between the income of Micro and Small Enterprises before and after obtaining financing from PT. PNM Mekaar